2015
DOI: 10.1371/journal.pone.0128757
|View full text |Cite
|
Sign up to set email alerts
|

Effect of JAK Inhibitors on Release of CXCL9, CXCL10 and CXCL11 from Human Airway Epithelial Cells

Abstract: BackgroundCD8+ T-cells are located in the small airways of COPD patients and may contribute to pathophysiology. CD8+ cells express the chemokine receptor, CXCR3 that binds CXCL9, CXCL10 and CXCL11, which are elevated in the airways of COPD patients. These chemokines are released from airway epithelial cells via activation of receptor associated Janus kinases (JAK). This study compared the efficacy of two structurally dissimilar pan-JAK inhibitors, PF956980 and PF1367550, and the glucocorticosteroid dexamethaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…v ‐1 ) collagen‐coated flasks. Cells were extracted from the lung tissues of healthy non‐smokers and COPD patients using methods described previously (Fenwick et al, ). COPD patients fulfilled the Global Initiative for Chronic Obstructive Lung Disease criteria (GOLD, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…v ‐1 ) collagen‐coated flasks. Cells were extracted from the lung tissues of healthy non‐smokers and COPD patients using methods described previously (Fenwick et al, ). COPD patients fulfilled the Global Initiative for Chronic Obstructive Lung Disease criteria (GOLD, ).…”
Section: Methodsmentioning
confidence: 99%
“…cDNA was diluted to 5 ng·μL −1 using RNase‐free water to be used for subsequent assays. Gene expression was measured using the Taqman real‐time PCR on a 7500 Real Time PCR system (Applied Biosystems, Paisley, UK) as described previously (Fenwick et al, ). mRNA expression levels of the samples were calculated using their C t values by interpolation from the standard curve constructed.…”
Section: Methodsmentioning
confidence: 99%
“…These chemokines are induced by IFNg through the activation of JAKs and phosphorylation of predominantly STAT1 (Tudhope et al, 2007). Pan-JAK inhibitors are effective in reducing IFNg-induced secretion of CXCR3-activating chemokines from human airway epithelial cells, demonstrating their potential as antiinflammatory treatments in COPD (Fenwick et al, 2015). B. Jakinibs.…”
Section: Janus-activated Kinase Inhibitionmentioning
confidence: 99%
“…On this basis, these associated signaling molecules have also been used as potential targets of anti-inflammatory treatment. It has been identified that the inhibition of JAK pathway in the airway epithelium may provide an alternative anti-inflammatory approach to glucocorticosteroid-resistant diseases in vitro (36). It has also been observed that the long-acting β2 agonists downregulate poly I:C-induced CXCL10 expression in bronchial epithelial cells via the β2 adrenoreceptor-cyclic adenosine monophosphate and JNK pathways in vitro (37).…”
Section: Expression Properties Of Epithelial Chemokinesmentioning
confidence: 99%